High-pressure processing of Manuka honey: brown pigment formation, improvement of antibacterial activity and hydroxymethylfurfural content - Fauzi, Noor Akhmazillah; Mohammed, M. Farid (Wiley-Blackwell Publishing Ltd, 2015)
This work was undertaken to assess the effects of high-pressure processing on brown pigment formation, antibacterial activity and hydroxymethylfurfural (HMF) content in Manuka honey. The honey was subjected to different pressures (200–600 MPa) at ambient temperatures (25–33 °C) and with moderate temperatures (53–74 °C) for holding times (10–30 min). The brown pigment formation in high-pressuretreated sample showed a significant increase (0.16–0.17, P < 0.05), whereas maximum percentage inhibition of Staphylococcus epidermidis (84.34 7.62%) was achieved when honey was subjected to 600 MPa as compared to the control (64.15 5.86%). The percentage inhibition in high-pressure-treated samples correlated linearly (r = 0.941) with brown pigment. No significant increase in HMF as affected by high pressure was found (P > 0.05). Thus, high-pressure processing has no adverse effect on the honey quality because it can control HMF concentration during process. Increasing brown pigment formation is associated with the enhancement of antibacterial activity.